Dynamic behavior of bubble forming at capillary orifice in methane oxidizing bacteria suspension. (July 2017) - Pei, Hong-Shan; Guo, Cheng-Long; Zhang, Guo-Feng; Tang, Qin-Yuan; Guo, Fei-Qiang
Graphical abstract: Dynamic behavior of bubble forming at capillary orifice in methane oxidizing bacteria suspension were observed experimentally under various gas flow rates. Highlights: The movement and adsorption of microorganism at the gas-liquid interface are observed experimentally. Dynamic behaviors of bubble forming at capillary orifice are investigated in suspension and pure water. Effect of gas flow rate on bubble formation evolution and departure process is revealed. The variations of bubble characteristic parameters during successive bubble formation are explored. Abstract: In this work, the dynamic behavior of bubble forming at capillary orifice was investigated using a developed bioreactor with methane oxidizing bacteria suspension as well as the movement and adsorption of microorganism at the gas-liquid interface were observed experimentally. The effect of gas flow rate from 0.8 to 1.45 mL/min on bubble formation evolution and departure process as well as the variations of equivalent departure diameter, departure volume and departure time of the leading bubble and the trailing bubbles were also explored during successive bubble formation. The experimental results showed that the chemotaxis effect and bubble expansion affected the movement and adsorption of microorganism at the gas-liquid interface, decreasing equivalent departure diameter and departure volume of the leading bubble as well as inrush number of the trailing bubble, shortening departure time of the leading bubble and inrush time of the trailing bubble, and prolonging waiting time of the leading bubble. Moreover, the increase of gas flow rate from 0.8 to 1.45 mL/min contributed to the increase of inrush number of the trailing bubble and the decrease of departure time of the leading bubble, but equivalent departure diameter and departure volume of the leading bubble were not much different under various gas flow rates. In addition, the trailing bubble merged into the leading bubble resulted in a significant fluctuation at the gas-liquid interface, affecting the bubble dynamic behavior and improving the mass transfer of gas mixture. These findings are beneficial to enhance the performance of the bioreactor by the optimal design of aeration system for bioconversion of methane fed into methane oxidizing bacteria suspension.